(3efSc GdeDjO HGddgs - (3CMeO Hf GdMSjf GdgGQhfjs
(3ChdgG (B:s
(3CeG HYO MeO ddg aEfi deG fXQJ ai GdeNJUQGJ GdehVhYGJ defGSc GdML hLOJgG eTJedI Ydi UaI GdML Ohf eYQaI hGLHGJg s
(3BNQgG (B:s
(3ef HGH GdEMQGe bhdg (B: (3hbO JeJ YeQJg gPG BNQ CHhGH GdML ef cJGH GdEaGOI ddeDjO HGddg Je GdefSc HMeO Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3cJHJ HYV GdYfGhjjf HGdUaQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis